PENGARUH KEBIJAKAN LARANGAN PENGGUNAAN HP TERHADAP FOKUS BELAJAR SANTRIWATI PONDOK PESANTREN MIFTAHUL HUDA KMA AL ULYA KALIJAMBE SRAGEN - Purwanto, Edi; Jabbaar, Ghozi Abdul; Rifai, Mukhamad; Masyriqi, Zufarudin Al (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine the effect of a mobile phone usage prohibition policy on the learning focus of female students at Pondok Pesantren Miftahul Huda Kuliyyatul Mu’allimat Al Ulya (KMA) Kalijambe Sragen. The research question posed is: How does the mobile phone prohibition policy affect the learning focus of female students in the pesantren environment? This study employed a quantitative descriptive approach using a survey technique. The population consisted of 40 female students selected through total sampling. The data collection instrument was a closed-ended Likert scale questionnaire comprising 21 items divided into two variables: the mobile phone prohibition policy and learning focus. Data were analyzed using descriptive statistical percentage analysis.The findings indicate that the majority of students are aware of, understand, and agree with the mobile phone prohibition policy implemented by the pesantren. Additionally, students reported an increase in their learning focus, characterized by improved concentration, a more conducive learning environment, and reduced digital distractions. These results reinforce the theory of Islamic learning environment management and Islamic character education, confirming that controlling technology use in Islamic boarding schools effectively enhances students’ academic focus.